A Case Study on the Readiness of 5th Grade Primary School Students on Understanding the Concept of Programming Languages through Minecraft - Demirkıran, Mustafa Can (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In this research, the orientations and problems of programming lessons were investigated using GBL to see the readiness of 5th grade students in computer courses. The study was carried out with a total of 63 participants who were studied in 5th grade in Eastern Mediterranean Doğa College. As a result of the collected questionnaire and interview questions, it turned out that the game-based learner helped the students in certain programming instruction which was the result of the participants’ answers. According to the results of study, the students found that the activity was educational and instructional through the GBL. In addition, the teaching and learning was successful at a certain level even though students look prejudiced on programming lessons. Keywords: Game-based learning, Minecraft, Programming courses, The readiness of primary school students.

ÖZ: Bu araştırmada 5’inci sınıf öğrencilerin programlama derslerindeki hazırbulunuşluklarını görmek amacıyla oyun-tabanlı öğrenim kullanılarak, programlama derslerine olan yönelimleri ve sorunları araştırılmıştır. Araştırma Doğu Akdeniz Doğa Koleji’nde toplamda 63 katılımcı ile yürütülmüştür. Katılımcıların katıldıkları dersin sonucunda uygulanan anket ve görüşme soruları ile toplanan veriler sonucunda, oyun-tabanlı öğrenmenin belli düzeyde programlama öğretiminde öğrencilere yardımcı olduğu ortaya çıkmıştır. İşlenen verilere göre, öğrenciler programlama derslerine önyargılı baksa dahi, oyun-tabanlı öğrenme sayesinde öğrenciler etkinliği eğitici ve öğretici bulmuş ve aynı zamanda oyunla öğretim belirli düzeyde başarılı olmuştur. Anahtar Kelimeler: Oyun tabanlı öğrenme, Minecraft, Programlama dersleri, İlkokul öğrencileri hazırbulunuşlukları
Master of Science in Computer and Instructional Technology Teacher Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2017. Supervisor: Dr. Tansu Hocanın.
Keywords: Information and Communication Technologies in Education; Information and Communication Technologies in Education; Game Based Learning-Educational games; Motivation in education; Game-based learning; Minecraft; Programming courses; The readiness of primary school students